Visualization of full-field stress evolution during 3D penetrated crack propagation through 3D printing and frozen stress techniques. (September 2020) - Liu, Peng; Ju, Yang; Fu, Guoming; Ren, Zhangyu
Highlights: Novel method reveals and quantifies full-field stress evolution around a 3D crack. 3D printing and frozen-stress techniques are used to measure 3D stress field. Crack depth affects the 3D stress field distribution near a penetrated crack. Stress variation along crack depth direction deflects non-planar crack propagation. Stress concentration on flaw tip contributes to crack initiation and propagation. Abstract: The initiation and propagation of a pre-existing three-dimensional (3D) fracture depends on the magnitude, distribution, and evolution of the full-field stress in the vicinity of the fracture. It is challenging for traditional fracture mechanics theories to directly reveal and accurately quantify the hidden stress field associated with 3D crack initiation and propagation. This is because the fracture propagation trajectory is a spatial, non-planar surface whose stress field is too complex to be accurately characterized by the existing theories. In this study, we report an experimental method to quantify the evolution of the 3D full-field stress along the depth of a penetrated crack via 3D printing technology, frozen-stress techniques, photoelastic testing, and phase-shifting methods. The results indicate that the 3D stress distribution undergoes obvious fluctuations along the depth direction of the penetrated crack. The variation of stress value along the depth direction indicates the deflection of the crack surface as the fracture approaches the free surface of the specimen. This study provides a promising method to reveal and quantify the hidden stresses that govern the non-planar propagation of a 3D fracture in solids.